Ambientación y decoración basado en el estilo moderno del restaurante cevicheria La Sirenita ubicado en la ciudad de Catamayo - Flores, Glenda Iliana (2015)
The aim of theproject was theatmosphere and decorbased onthe modern style, applying the knowledge acquired during. Technology inInterior Design andDecorationEnvironmentsat the National UniversityofLoja.Theproposed businesswill be located inthein the streetEugenio EspejoandOctober 9, is currentlylaboringin order tobe provided inthe marketin orderto competenot onlywithadvertising objects, but alsowith other factors,basicpositioning, differentiation,idealization, for itestablishedtactics thatleadto fulfillmentfinallya design isdeveloped throughsketches, using moderncolorsthat appealto the eyeof customers. In the interior design in terms of applying styles and trends should be selected according to the medium or environment, taking into account national and local culture including; the architectural structure, decorations, colours, textures, and furniture from these base elements can make a decoration, in order to obtain aesthetic and functional results according to studio space. this research aims, raise a design proposal called "Atmosphere and decoration based on the Modern Style Restaurant Cevicheria " La Sirenita "located on the careful Catamayo" applying modern style to have favourable results for this work area, using decorative materials, colours, furniture, symmetrical elements that create a harmonious, functional and welcoming atmosphere.